The role of speech style, frequency, and density in recognition memory for spoken words - Pycha, Anne; Culleton, Tessa; Song, Jae Yung (Frontiers in Psychology, 2024)
What determines whether listeners remember a spoken word? The Effortfulness Hypothesis claims that memory is modulated by a word’s intelligibility during real-time processing, while the Distinctiveness Hypothesis claims that it is modulated by a word’s distinguishing characteristics. We tested these differing predictions using American English words that varied along three dimensions known to affect both intelligibility and distinctiveness: speech style (clear versus casual), frequency (high versus low), and neighborhood density (high versus low). In a recognition memory experiment, participants (n = 66) listened to a set of study words, and then gave yes/no judgments to indicate whether or not they had heard the word earlier. Results showed that those words which exhibited distinctive characteristics – whether due to clear speech style, low frequency, or low density – were remembered better. The finding supports the Distinctiveness Hypothesis, suggesting that our capacity for remembering words relies on their distinctiveness, rather than on our capacity for recognizing them in real time.